A health service for the nation (London : published by the Women Public Health Officers' Association)
1943-03-27 1943 1940s 8 pages 31. We suggest therefore that the Health Services available at Local Health Centres and Divisional Treatment Centres respectively might be :— LOCAL HEALTH CENTRE. 1. HOME DOCTORS' SERVICE. 2. ANTE-NATAL AND POSTNATAL SESSIONS. 3. PERIODICAL MEDICAL AND DENTAL EXAMINATIONS of infants and toddlers. 4. MEDICAL AND DENTAL INSPECTION OF SCHOOL CHILDREN. We suggest that classes or groups of school children should attend the Health Centre for examination, thus avoiding both the unsatisfactory conditions for examinations in schools, and the disturbance of more than one class. We believe that school medical inspections should take place annually and dental inspections every six months. 5. OTHER PERIODICAL MEDICAL AND DENTAL EXAMINATIONS, including those in connection with industrial employment. 6. CLASSES IN PARENTCRAFT. These would be facilitated if the Health Centre were in the same building as a Domestic Subjects and/or Manual Training Centre. 7. PHYSICAL TRAINING for all ages and both sexes. 8. FORMAL HEALTH TEACHING. 9. PSYCHOLOGICAL AND CHILD GUIDANCE CLINICS. We believe that patients will attend Health Centres more readily than a Treatment Centre or Hospital. DIVISIONAL TREATMENT CENTRE. 1. CONSULTANTS' SESSIONS. 2. PHYSIO-THERAPY. 3. X RAY EXAMINATION, INCLUDING RADIOGRAPHY. 4. LABORATORY SERVICES. 5. TUBERCULOSIS DISPENSARY SERVICE for T.B. patients. We suggest that the periodical examination of contacts should be undertaken at the local Health Centre or, in exceptional cases, their own homes. 6. REHABILITATION AND OCCUPATIONAL THERAPY. 7. DISPENSARY FOR DRUGS. Also supplying Home Doctors at Local Health Centres. 27th March, 1943 PUBLISHED BY THE WOMEN PUBLIC HEALTH OFFICERS' ASSOCIATION, 5 VICTORIA STREET, LONDON, S.W.1. AND PRINTED BY FARMER & SONS, LTD., 295 EDGWARE ROAD, LONDON, W.2. 292/847/2/155